THE PHENOMENON OF GOTONG ROYONG IN JAVA COMMUNITY: A CASE STUDY NYUMBANG - Ari Prasetiyo (Indonesian Journal of Multidisciplinary Science, 2022)
Culture is the result of human creation in order to make life easier. Along with the times, the culture is possible to experience shifts and changes. This study discusses one of the cultures of gotong royong in Javanese society, especially the nyumbag, by taking research samples from several villages in Yogyakarta. This study discusses the changes and phenomena of people's attitudes toward the tradition of donating. The results of the study found that on the one hand the community was uncomfortable and objected to the tradition of donating, but on the other hand the community was unable to change the tradition. This is due to the existing system in the community, namely in the form of social control and social sanctions. These two things greatly affect the mindset and behavior of the community. Social control and social sanctions are factors that keep the continuity of a hereditary tradition in society.